Teaching Mathematics Remotely From The Perspective Of Parents And Teachers In Primary And Secondary Schools In The Kingdom Of Saudi Arabia - Dr. Hamad Abdullatif Al-Hulaibi (Migration Letters, 2024)
This study aimed to identify teaching mathematics remotely from the point of view of parents and teachers. The sample included (122) parents whose children teach mathematics, and (41) teachers who teach mathematics. The purposive sample was chosen. The results showed that the arithmetic averages for (the extent to which parents follow their students while teaching mathematics remotely) are between (3.51 and 1.73), where (follow-up) and (I make a suitable place for my son/daughter during distance learning) and (I know and understand the use of... Distance learning programs) at an intermediate level. Finally, (my son/daughter benefits more from distance education compared to in-person mathematics education) at a low level. The arithmetic averages for (the extent of par[1]ents’ satisfaction with mathematics teachers while teaching them...) are between (3.80 and 1.69), where (satisfaction) is at an average level, while the two paragraphs (mathematics teachers work very hard...) ranked first, as well as the item (The mathematics teacher understands the use of ...) ranked second, which were at a high level. Finally, (mathematics is suitable for distance teaching for the lower grades...) at a low level. The arithmetic averages for (the extent of possession of distance teaching skills among mathematics teachers) ranged between (3.54 and 1.29), where (the degree of possession of teaching skills) was at an average level, and the two items (I work very diligently and diligently while teaching remotely) ranked first. And (I understand the use of remote programs and strategies...) at a high level. Finally, (mathematics is suitable for distance teaching for the lower grades...) at a low level. The arithmetic averages for (the extent of parents’ knowledge of teaching mathematics remotely from the point of view of male and female teachers) were between (3.41 and 1.39), where they were (parents’ knowledge of teaching mathematics remotely from the point of view of..) and (parents always help Their children in solving problems...) and (Parents prefer that distance education be in the evening) at an average level. Finally, (parents prefer distance teaching instead of in-person) at a low level. There are no statistically significant differences in the extent to which parents follow up on their student children while they teach mathematics remotely, due to the relationship of kinship and the marital status of the parents, as well as the extent to which mathematics teachers possess distance teaching skills, due to some demographic variables represented by gender and academic stage. Department of Curriculum and Instruction, College of Education, Imam Abdulrahman Bin Faisal University, Dammam 31451, Saudi Arabia.